The prognostic role of γδ T cells in colorectal cancer based on nomogram - Rulan Ma; Meijun Gong; Tuanhe Sun; Lin Su; Kang Li (European Journal of Medical Research, 2023)
Abstract Objective The aim of the present study was to explore the prognostic role of γδ T cells in colorectal cancer, and establish a nomogram for predicting the survival of the patients. Methods Immunohistochemistry was performed to analyze the infiltration degree of γδ T cells in tumor and normal tissues of colorectal cancer. The relationship between γδ T cells infiltration in tumor tissues and the prognosis of patients with colorectal cancer were determined by Cox regression analysis and survival analysis. R software was used to establish and verify a nomogram for predicting the prognosis of patients with colorectal cancer. Results The degree of γδ T cell infiltration in tumor tissues and normal tissues of CRC was not different (t = 0.35, P = 0.73). However, the infiltration of γδ T cell was related to the survival status of the patients (x 2 = 4.88, P = 0.03). Besides, the infiltrating degree of γδ T cells in tumor tissue was obviously related to the prognostic improvement of the patients with colorectal cancer (log-rank P = 0.02) and could reflect the benefit of adjuvant chemotherapy. The nomogram based on tumor diameter, tumor location, AJCC stage, chemotherapy, serum CEA level and γδ T cell infiltration was established and could provide a reference for predicting the survival of colorectal cancer patients. Conclusion γδ T cell infiltration degree in tumor tissue was an important factor to improve the outcome of patients with colorectal cancer, and can predict the benefit of adjuvant chemotherapy.